2015
DOI: 10.1002/jaal.476
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned

Abstract: This paper describes a case study of how a middle school literacy coach and a science teacher attempted to improve disciplinary literacy teaching in a sixth‐grade science class. The collaborative inquiry exposed the disciplinary knowledge gap of the literacy coach (a former language arts teacher) and the science teacher's limited knowledge of literacy instruction. These shared disciplinary knowledge gaps necessitated the co‐construction of collaborative practices to ameliorate the tension and improve disciplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…For example, Warren (2013) wrote, As Moje described it, disciplinary literacy is "a matter of teaching students how the disciplines are different from one another, how acts of inquiry produce knowledge and multiple representational forms…, as well as how those disciplinary differences are socially constructed" (p. 103). (p. 392) Similarly, the articles reviewed indicate that disciplines are distinct and that disciplinary literacy focuses on the habits of mind used by disciplines (e.g., Warren, 2013;Wilder & Herro, 2016). However, Warren went on to wonder what role English language arts (ELA) teachers and literacy faculty will play in facilitating disciplinary literacy programs and suggested that they should collaborate with math, social studies, and science educators to emphasize rhetorical reading as a practice that most disciplines employ.…”
Section: How Does the Existing Literature In Jaal Define Disciplinarymentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Warren (2013) wrote, As Moje described it, disciplinary literacy is "a matter of teaching students how the disciplines are different from one another, how acts of inquiry produce knowledge and multiple representational forms…, as well as how those disciplinary differences are socially constructed" (p. 103). (p. 392) Similarly, the articles reviewed indicate that disciplines are distinct and that disciplinary literacy focuses on the habits of mind used by disciplines (e.g., Warren, 2013;Wilder & Herro, 2016). However, Warren went on to wonder what role English language arts (ELA) teachers and literacy faculty will play in facilitating disciplinary literacy programs and suggested that they should collaborate with math, social studies, and science educators to emphasize rhetorical reading as a practice that most disciplines employ.…”
Section: How Does the Existing Literature In Jaal Define Disciplinarymentioning
confidence: 99%
“…The possible solution the two authors proposed is to "create and sustain equal, productive collaboration" (p. 629) in which both parties enter the partnership with shared goals and engage in joint planning, teaching, and assessment. Wilder and Herro (2016) offered an example of such a collaboration between a science teacher and a literacy coach who worked together to develop knowledge of disciplinary literacy and to teach from a disciplinary literacy perspective. Authors also maintained that literacy faculty can help content area teachers (a) develop, select, or modify generic content area strategies/practices that will help students learn disciplinary literacy (Brozo et al, 2013;Siebert et al, 2016;Warren, 2013), and (b) "figure out how to plan instruction that includes not only textbooks but the types of texts that are part of the discipline, and to let those texts dictate what discipline-based literate practices are taught" (Hynd- Shanahan, 2013, p. 96).…”
Section: How Is Collaboration Represented In Existing Literature Aboumentioning
confidence: 99%
See 2 more Smart Citations
“…
When both members of a coaching dyad are professional educators possessing unique expertise, the potential of bidirectional learning can be realized (Wilder & Herro, 2016). In the state in which this study took place, those certified to teach ELs take courses in linguistics, language acquisition, grammar, culture, and literacy and
…”
mentioning
confidence: 99%